Estimating Value-at-Risk for the g-and-h distribution: an indirect inference approach. Issue 8 (3rd August 2019) - Bee, M.; Hambuckers, J.; Trapin, L.
Abstract : The g-and-h distribution is able to handle well the complex behavior of loss data and applied to operational losses suggests that indirect inference estimators of VaR outperform quantile-based estimators